The Characterization of OXA-232 Carbapenemase-Producing ST437 Klebsiella pneumoniae in China - Xingbei Weng; Qiucheng Shi; Sheng Wang; Yubo Shi; Dinghe Sun; Yunsong Yu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) was epidemic around the world and become a global threat to public health. The most important carbapenem-resistant mechanism is producing carbapenemases, especially Klebsiella pneumoniae carbapenemase (KPC), which is prevalent in the international clonal complex CC11. The high-risk multidrug-resistant CC11 is widespread worldwide, and KPC-producing and (New Delhi metallo) NDM-producing strains had been reported in this clonal complex before; moreover, cases with the CC11 strain faced more severe forms of drug resistance and treatment challenges than other clonal complexes. In this study, we identified an OXA-232-producing ST437 Klebsiella pneumoniae isolate in China, which belonged to CC11. The isolate was resistant to β-lactams, aminoglycosides, and fluoroquinolones but susceptible to fosfomycin, tigecycline, and colistin. The blaOXA-232 gene was located on a 6141 bp ColKP3-type nonconjugative plasmid, and the plasmid was transformed by chemical transformation successfully. This is the first report of OXA-232-producing ST437 K. pneumoniae in China, a new clone of high-risk multidrug-resistant CC11.